2020
DOI: 10.14814/phy2.14534
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microparticle concentrations across acute and chronic cardiovascular disease conditions

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Clinical ASCVD development is associated with high release of EVs. Assessment of vascular status is crucial for atherosclerosis prevention and to this aim EVs can serve as potential biomarkers in the clinics [ 38 , 232 ]. Molecular footprints of EVs provide clues about their cellular origin under healthy and diseased states, configuring a precious biomedical tool for liquid biopsy, easily detectable in body fluids.…”
Section: Extracellular Vesicles As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical ASCVD development is associated with high release of EVs. Assessment of vascular status is crucial for atherosclerosis prevention and to this aim EVs can serve as potential biomarkers in the clinics [ 38 , 232 ]. Molecular footprints of EVs provide clues about their cellular origin under healthy and diseased states, configuring a precious biomedical tool for liquid biopsy, easily detectable in body fluids.…”
Section: Extracellular Vesicles As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…Changes in circulating EVs of different cellular origin have been widely reported for almost all cardiovascular risk factors [ 233 , 234 , 235 , 236 ] and pathologies [ 237 , 238 , 239 ] reflecting their pathophysiological severity. Beyond diagnostic use, EVs have been suggested for the prediction of major adverse cardiovascular events (MACE) [ 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 ] and mortality [ 244 ]. Circulating procoagulant MVs were found at higher levels in patients with ACS than healthy subjects [ 238 , 239 , 240 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 ].…”
Section: Extracellular Vesicles As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…These findings indicate that endothelial activation participates in the pathogenesis of coronary artery disease by using E-selectin molecule [18]. Recently Landers-Ramos et al [19] revealed that the number of CD62E + endothelial microparticles was higher in the coronary artery disease (265.6 ± 96.1 particles/µL) compared with the healthy subjects (167.6 ± 32.1 particles/µL), but this did not reach statistical significance. The reasons for this contradiction may be due to smaller sample sizes used in this study and a significant difference in the total number of medications taken between patients with coronary artery disease (9.4 ± 1.3) compared to healthy controls (4 ± 1.1) [19].…”
Section: Biomarkers Of Endothelial Activation In Cardiovascular Diseasesmentioning
confidence: 91%
“…Recently Landers-Ramos et al [19] revealed that the number of CD62E + endothelial microparticles was higher in the coronary artery disease (265.6 ± 96.1 particles/µL) compared with the healthy subjects (167.6 ± 32.1 particles/µL), but this did not reach statistical significance. The reasons for this contradiction may be due to smaller sample sizes used in this study and a significant difference in the total number of medications taken between patients with coronary artery disease (9.4 ± 1.3) compared to healthy controls (4 ± 1.1) [19]. Moreover, endothelial microparticles were also found in peripheral vascular diseases (e.g., microscopic polyangiitis, polyarteritis nodosa, Takayasu arteritis etc.)…”
Section: Biomarkers Of Endothelial Activation In Cardiovascular Diseasesmentioning
confidence: 91%
See 1 more Smart Citation